Productive hybrid learning environments in times of transition : a multiple case study in higher education health contexts : a thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy at Te Kunenga ki Pūrehuroa Massey University - Green, Jennifer K. (Massey University, 2026)
Higher education health contexts have incorporated hybrid learning environments for over three decades with varying degrees of acceptance. Responses in educational institutions to the Covid-19 pandemic highlighted the need for an understanding of how digitally-mediated learning might extend students’ experiences beyond physical classrooms. Drawing on ecological perspectives in education, learning is foregrounded as part of a complex web of elements contributing to productive learning environments. Anchored in postdigital learning contexts with consideration for the influences of Networked Learning principles, Activity-Centred Analysis and Design (ACAD) is used as an analytical framework to discuss the study findings from multiple case studies that explore student and academic staff perspectives in higher education. These theoretical frameworks informed the systematic literature review (𝘯=21) incorporating a framework synthesis approach to identify potential contributors for productive, hybrid learning environments. In combination, the body of literature and chosen theoretical frameworks laid the foundation for this multiple case study research to explore and answer the thesis questions identifying the characteristics of productive, hybrid learning environments in higher education health contexts. The cases include undergraduate courses in health disciplines encompassing nursing, pharmacology and social work. Data was generated through observations of teaching and course artefacts, and semi-structured participant interviews. The ACAD framework allows examination of relationships between tools, tasks and social arrangements and explores their influence on student learning activities in postdigital contexts. The experience of learners in different locations and disciplines and educators adapting to the transition to hybrid environments, identifies contributors to productive learning environments. Cross-case analysis shows tangible, flexible and timely support for students creates a learning environment that is safe, enjoyable and supports students through personal, professional and academic challenges. Additionally, course design with a consistent format, flexible access and purposefully curated content focused on preparing students for graduate practice, contributes to productive learning environments. A clear understanding of foundational learning principles within a dynamic, collaborative and cohesive teaching team can assuage the challenge of unpredictable pandemic-associated learning design requirements. Importantly, markers of productive, hybrid learning environments in higher education health contexts include the creation of rich, realistic teaching and learning opportunities using resources commonly found in professional practice contexts. These experiential opportunities support the development of skill proficiency and incorporate intentional challenge to equip students for professional growth. Together, these findings indicate productive, hybrid learning environments incorporate a range of intentional design for learning considerations to effectively support students, faculty, and to create rich, realistic teaching and learning opportunities. By taking an ecological stance, this multiple case study research draws on and extends the ACAD framing to propose an approach to actualise productive learning environments in HE health contexts. The novel Aotearoa Design for Learning Framework combines the dimensions of the ACAD framework with the principles of Te Whare Tapa Whā to support exploration of design and analysis of teaching and learning within healthcare education in the Aotearoa New Zealand cultural context. Other key contributions to new knowledge include 11 principles for the design of productive, hybrid learning environments in the health disciplines and a self-auditing tool to support teacher professional development. This thesis contributes to extant knowledge by identifying imperatives of design for learning in post-digital contexts for hybrid learning environments to be productive.
Keywords: Hybrid learning environments; Higher education; Multiple case study; Nursing; Pharmacology; Social work; Study and teaching (Higher); New Zealand; Curriculum planning; Blended learning; Case studies; 4205 Nursing; 4409 Social work; 321401 Basic pharmacology; 39 Education::3901 Curriculum and pedagogy::390110 Medicine, nursing and health curriculum and pedagogy